REFERENCE OVERVIEW ON DESIGN AND SIMULATION OF GREEN SUPPLY CHAIN MANAGEMENT - Ihsan, Muhammad Alif; Risonarta, Victor Yuardi (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
The issue of decreasing air quality index due to supply chain transportation is one of the problems that must be addressed by the manufacturing sector. Green supply chain management (GSCM) can be a solution to address environmental issues in the supply chain. The GSCM is an integrated view that incorporates environmental considerations into the conventional supply chain, ranging from supplier selection, product design, material selection, manufacturing processes, packaging, and distribution. The correct implementation of GSCM can address both environmental and performance issues, e.g. decreasing both energy consumption and air pollution. The GSCM consists of green design, green manufacturing, green logistics, disassembly, and remanufacturing. To address the GSCM issues, the simulation is also discussed in this work. Meanwhile, this work suggests more policies for recycling, remanufacturing, and reuse of obsolete manufacturing products to support GSCM in developing nations.